PENINGKATAN PEMAHAMAN DALAM PENCEGAHAN PERILAKU MEROKOK MELALUI LAYANAN BIMBINGAN KELOMPOK DENGAN MEDIA KERTAS (KARTU EDUKASI REMAJA TANPA ASAP) PADA SISWA KELAS VII SMPN 3 BANJARMASIN - Rosalinda, Wennie; Fatimah, Siti; Nurhafifah, Nurhafifah; Permata Sari, Nina; Istiqomah, Istiqomah; Riyadi, Akhmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low level of students' understanding of the dangers of smoking is a common problem among junior high school students, influenced by peer pressure, curiosity, and the lack of engaging educational media. Based on the Student Needs Questionnaire (AKPD) conducted at SMPN 3 Banjarmasin, several students demonstrated a low level of understanding regarding the dangers of smoking and smoking prevention efforts. This study aimed to improve students’ understanding of smoking prevention through group guidance services using KERTAS (Smoke-Free Youth Education Card) media. The study employed the Guidance and Counseling Action Research (PTBK) method, conducted in three cycles consisting of planning, action, observation, and reflection stages. The participants were 10 seventh-grade students with low understanding of the dangers of smoking. Data were collected through observation, tests, and documentation, while descriptive analysis is used to present the results across pre-cycle, cycle I, cycle II, and cycle III. The findings showed a gradual and significant improvement in students’ understanding. In the pre-cycle, all students were categorized as low. After the intervention, 60% of students reached the high category and 40% the very high category in cycle I. In cycles II and III, 70% achieved the very high category and 30% remained in the high category, with three students obtaining perfect scores in cycle III. Process evaluation also indicated improvements in participation, self-confidence, critical thinking, and active engagement. Therefore, group guidance services using KERTAS media were effective in enhancing students’ understanding of the dangers of smoking and supporting early smoking prevention efforts.